2016
DOI: 10.1136/thoraxjnl-2015-207876
|View full text |Cite
|
Sign up to set email alerts
|

Exome-wide analysis of rare coding variation identifies novel associations with COPD and airflow limitation inMOCS3,IFIT3andSERPINA12

Abstract: BackgroundSeveral regions of the genome have shown to be associated with COPD in genome-wide association studies of common variants.ObjectiveTo determine rare and potentially functional single nucleotide polymorphisms (SNPs) associated with the risk of COPD and severity of airflow limitation.Methods3226 current or former smokers of European ancestry with lung function measures indicative of Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2 COPD or worse were genotyped using an exome array. An ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…For example, one previous study investigated the association between genetic variants in the coding regions of the CHRNA3‐CHRNA5‐CHRNB4 genes and COPD risk in Chinese using direct exon sequencing and found that three rare missense variations contributed to increased risk of COPD and worsen lung functions . In addition, other evidence showed a newfound low frequency non‐synonymous SNP in MOCS3 and a rare variant in IFIT3 to be associated with the risk of COPD and severity of airflow limitation . In our study, we observed a significant link of p.Glu116Lys rare variant in MAP2K7 to COPD risk and found that this rare variant could explain about 1.92% of COPD heritability.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…For example, one previous study investigated the association between genetic variants in the coding regions of the CHRNA3‐CHRNA5‐CHRNB4 genes and COPD risk in Chinese using direct exon sequencing and found that three rare missense variations contributed to increased risk of COPD and worsen lung functions . In addition, other evidence showed a newfound low frequency non‐synonymous SNP in MOCS3 and a rare variant in IFIT3 to be associated with the risk of COPD and severity of airflow limitation . In our study, we observed a significant link of p.Glu116Lys rare variant in MAP2K7 to COPD risk and found that this rare variant could explain about 1.92% of COPD heritability.…”
Section: Discussionsupporting
confidence: 62%
“…31 In addition, other evidence showed a newfound low frequency non-synonymous SNP in MOCS3 and a rare variant in IFIT3 to be associated with the risk of COPD and severity of airflow limitation. 29 In our study, we observed a significant link of p.Glu116Lys rare variant in MAP2K7 to COPD risk and found that this rare variant could explain about 1.92% of COPD heritability. All the above suggested that p.Glu116Lys rare variant in MAP2K7 might be a genetic marker for COPD susceptibility.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Four of the datasets in our metaanalysis were previously investigated for genetic associations for COPD status (18), so our results are enriched for previously discovered associations. In addition, genotyping was performed before the results of recent COPD and lung function GWAS studies by the UK BiLEVE group (7) and Soler Artigas and colleagues (57,58) were published, and the additional risk loci for COPD and lung function found in these studies were not included in our analysis. We chose to use a simple model for our genetic (and clinical) risk scores.…”
Section: Original Researchmentioning
confidence: 99%